Digital pen with keyboard functionality - Raju, Yadil Alam; Rimon, Rakib Hassan; Mehedi, Md.Mohiuddin (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.